Spinal Pseudoarthrosis: A Rare Complication in Psoriatic Arthritis - Ko-Jen Li; Chia-Li Yu; Song-Chou Hsieh; Ping-Ning Hsu (Journal of the Formosan Medical Association, 2006)
Discovertebral erosion with pseudoarthrosis is a well-known complication in ankylosing spondylitis but it is seldom mentioned in psoriatic arthritis. We report a 53-year-old woman with an 8-year history of pso-riatic arthritis who developed severe low back pain followed by sudden onset of numbness in the lower limbs, weakness and dysesthesia. Abnormal contour of L1 and L2 vertebrae and intervertebral disc space was noted during radiologic examination. Pseudoarthrosis was suspected based on extensive osseous re-sorption and reactive sclerosis about the discovertebral junction on magnetic resonance imaging study. She underwent emergency operation due to spinal instability with neurologic deficit. Pseudoarthrosis was confirmed intraoperatively. No evidence of infection or neoplasms was found. This case shows that pseudoarthrosis can be complicated in patients with psoriatic arthritis, and this possibility should be considered in patients with previously quiescent disease.